2021
DOI: 10.1080/01446193.2021.1876894
|View full text |Cite
|
Sign up to set email alerts
|

BIM uses for deconstruction: an activity-theoretical perspective on reorganising end-of-life practices

Abstract: Despite that Building Information Modelling (BIM) is often praised as a whole life-cycle methodology, possibilities for deconstruction are consistently overlooked. This study demonstrates what those possibilities may be. Previous studies showed that: deconstruction practices pose several site-based challenges; BIM implementations may help practitioners to address such challenges; and activity theory offers a framework to understand BIM implementations. We aimed to explore how deconstruction practices can be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Although rarely seen, BIM can also be used in deconstruction activities where the digital copy of the building does not exist. To this end, van der Berg et al [170] demonstrated in a case study that BIM could be used for analysing the existing condition of the site, labelling reusable elements and performing deconstruction planning simulations.…”
mentioning
confidence: 99%
“…Although rarely seen, BIM can also be used in deconstruction activities where the digital copy of the building does not exist. To this end, van der Berg et al [170] demonstrated in a case study that BIM could be used for analysing the existing condition of the site, labelling reusable elements and performing deconstruction planning simulations.…”
mentioning
confidence: 99%
“…Deconstruction or selective deconstruction or selective, systematic dismantling, also known as construction in reverse, is a strategy which, unlike mechanical demolition, aims to maximize the recovery of building parts when taking apart a building for future relocation and reuse and, consequently, to minimize construction waste (Bertino, 2021; Forghani et al , 2021; Marzouk and Elmaraghy, 2021; O’Grady et al , 2021; Bukunova and Bukunov, 2020; Jockwer et al , 2020; Kibert, 2016; Rios et al , 2015; Thomsen et al , 2011). The term deconstruction has been associated with the removal of demountable building parts to claim their residual value for reuse (Cambier et al , 2021; Akinade et al , 2020) and to building disassembly for material, element or component reuse (Guerra and Leite, 2021; van den Berg et al , 2021; Akinade et al , 2015). Cambier et al (2021) distinguish deconstruction from disassembly by the possibility to claim the value of a building part or to reuse it as is.…”
Section: Proposed Taxonomymentioning
confidence: 99%
“…Queheille et al [6] suggested a Multi-Objective Optimization algorithm that works out a deconstruction strategy according to predefined cost, time, and recovery rate goals; the obtainable results strongly depend on Deconstruction companies' assumptions and predictions on the work efficiencies. Different authors also highlighted the role of BIM in supporting CE-oriented decision-making during the pre-demolition phase [7,8,9,10]. BIM helps in analyzing the existing conditions of the demolition site, scheduling demolition/deconstruction activities, classifying or quantifying CDW, and tracking reusable components; however, on-site workers of demolition companies could be unprepared for using BIMbased methods [7], and BIM reconstruction of a demolition site and related reverse engineering process can be challenging (e.g., data capturing devices as 3D Laser scanner [9] may be necessary).…”
Section: Introductionmentioning
confidence: 99%
“…Different authors also highlighted the role of BIM in supporting CE-oriented decision-making during the pre-demolition phase [7,8,9,10]. BIM helps in analyzing the existing conditions of the demolition site, scheduling demolition/deconstruction activities, classifying or quantifying CDW, and tracking reusable components; however, on-site workers of demolition companies could be unprepared for using BIMbased methods [7], and BIM reconstruction of a demolition site and related reverse engineering process can be challenging (e.g., data capturing devices as 3D Laser scanner [9] may be necessary). These approaches are time-consuming and often affordable only for large projects and/or big companies.…”
Section: Introductionmentioning
confidence: 99%